Analisis fatwa zakat di Malaysia dari perspektif maqasid syariah / Azri Bhari - Azri, Bhari (2016)
The nature of Islamic legal practice in Malaysia is well known for its adhering to the view of Shafie madhab in fiqh issues based on the historical background of the arrival of Islam in Malaysia and Islamic legal practice that have been adapted. Fatwa issued by the fatwa institution in Malaysia is evolving from time to time in accordance to the principles of Islamic law, which is flexible and accommodating the changing environment. In recent years, the development of Islamic legal practice shows the ultimate determination of fatwa especially on zakat are no longer bound to Shafie madhab. This shows an openness in considering the views of other madhab and opinion of contemporary fiqh scholar in issuing law or fatwa related to zakat. This can be seen on the scenario of fatwa that shifted from Shafie madhab to view of other madhab and opinion of contemporary fiqh scholar. Based on this fatwa scenario on zakat in Malaysia, there are needs to analyse the changes of fundamental views of fatwa on zakat to other madhab as well as taking into consideration the needs to achieve the principles of maqasid al-shariah. This study determine 26 fatwa on zakat that shifted from Shafie madhab to others out of from 191 fatwas that have been classified into six themes. The study also reviews the principles of maqasid al-shariah that has been deliberated in determining the fatwa on zakat. This qualitative study is conducted using data collection methods and analysis of this data collection focuses on the fatwa on zakat issued by various fatwa institutions in Malaysia consisted of the gazetted fatwa as well as and non-gazetted fatwa that has been published in books and government gazette or broadcast via the official fatwa portal of JAKIM. Data collections are conducted through library research and interviews. Data obtained in the form of content analysis is analysed using inductive, deductive and comparative studies to produce results. Finding shows that there are numbers of fatwa on zakat shifted from Shafie madhab. This study also details the maqasid al-shariah deliberated in fatwa on zakat. It can be concluded that mufti and fatwa committee in Malaysia strive to achieve the maqasid al-shariah from the maṣlaḥah and mafsadah perspectives in determining fatwa on zakat.